2020
DOI: 10.1016/j.ymthe.2019.11.016
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: METTL14 Suppresses CRC Progression via Regulating N6-Methyladenosine-Dependent Primary miR-375 Processing

Abstract: Epigenetic alterations contributed to human carcinogenesis immensely. N6-methyladenosine (m6A) is one of the most preventive and abundant modifications on RNA molecules present in eukaryotes. However, the biological function of m6A methylation in colorectal cancer (CRC) remains largely unclear. Here, we found that METTL14 was downregulated in CRC tissues and cell lines, and closely correlated with overall survival (OS). METTL14 knockdown significantly reduced m6A levels in total RNAs and promoted CRC cell grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
152
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(159 citation statements)
references
References 42 publications
7
152
0
Order By: Relevance
“…In hepatocellular carcinoma (HCC), METTL14 has been proven to promote pri-miR-126 processing, while METTL14 depletion in HCC cells reduces m 6 A levels and miR-126 expression, leading to cancer cell migration and invasion [17]. In another study, METTL14 was found to suppress CRC progression by promoting the m 6 A-dependent maturation of miR-375, which could not only inhibit cancer cell proliferation by targeting Yes-associated protein 1 (YAP1), but also suppress cancer cell migration and invasion through the miR-375/SP1 pathway [38]. Furthermore, the downregulation of METTL14 is closely related to malignant progression and poor recurrence-free survival (RFS) and overall survival (OS) of patients, suggesting the potential role of METTL14 in predicting tumor metastasis and recurrence [17,38].…”
Section: Roles Of M 6 a Methylation On Ncrnas In Cancer Micrornasmentioning
confidence: 99%
See 1 more Smart Citation
“…In hepatocellular carcinoma (HCC), METTL14 has been proven to promote pri-miR-126 processing, while METTL14 depletion in HCC cells reduces m 6 A levels and miR-126 expression, leading to cancer cell migration and invasion [17]. In another study, METTL14 was found to suppress CRC progression by promoting the m 6 A-dependent maturation of miR-375, which could not only inhibit cancer cell proliferation by targeting Yes-associated protein 1 (YAP1), but also suppress cancer cell migration and invasion through the miR-375/SP1 pathway [38]. Furthermore, the downregulation of METTL14 is closely related to malignant progression and poor recurrence-free survival (RFS) and overall survival (OS) of patients, suggesting the potential role of METTL14 in predicting tumor metastasis and recurrence [17,38].…”
Section: Roles Of M 6 a Methylation On Ncrnas In Cancer Micrornasmentioning
confidence: 99%
“…[35] Promote pri-miRNA processing miR-1246 Promote cell migration in CRC [36] Promote pre-miRNA processing miR-143-3p Promote the brain metastasis of NSCLC [37] Promote pri-miRNA processing miR-25 Promote cell proliferation in pancreatic cancer [41] Modulate the structure of lncRNA MALAT1 Promote cell proliferation [13] Stabilize lncRNA and enable the ceRNA model LINC00958 Promote HCC lipogenesis and progression. [60] Stabilize lncRNA and enable the ceRNA model MALAT1 Promote NSCLC drug resistance and metastasis [61] Promote lincRNA-let-7 interaction Linc1281 Regulate pluripotency and differentiation of mESC [62] METTL14 Promote pri-miRNA processing miR-126 Suppress HCC metastasis [17] Promote pri-miRNA processing miR-375 Suppress CRC progression [38] Modulate the structure of lncRNA MALAT1 Promote cell proliferation [13] WTAP, RBM15, RBM15B On the other hand, the observation that higher expression of miRNAs is usually accompanied by a higher proportion of m 6 A-modified target transcripts suggests that miRNAs may regulate m 6 A abundance on their target transcripts [7]. Consistently, Chen et al reported that miRNAs could modulate m 6 A formation on mRNAs by promoting the binding of METTL3 through a sequence pairing mechanism, which increased m 6 A levels and allowed the reprogramming of mouse embryonic fibroblasts (MEFs) into pluripotent stem cells [85].…”
Section: Ncrnas Regulate M 6 a Methylation On Mrnas In Cancer Mirnasmentioning
confidence: 99%
“…m6A modification had been proved to be enriched in near stop codon and 3′untranslated terminal region (UTR) and translate near 5′UTR in a cap-independent manner [3]. m6A RNA modification of various RNAs, including messenger RNAs (mRNAs) [4], microRNAs (miRNAs) [5] and long non-coding RNAs (lncRNAs) [6], was a dynamic and reversible posttranscriptional modification process maintained by three different types of protein complex, including m6A readers, writers, and erasers [7]. This dynamic and reversible nature of the m6A modification made it pivotal in the rapid cellular communication.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic protein methyltransferase-like 14 (METTL14) participates in mediate cellular N 6 -methyladenosine (m 6 A) deposition [ 10 ] and is closely related to the occurrence and development of malignant tumors [ 11 23 ]. METTL14 plays a complex role in malignant tumors: low levels of METTL14 expression are found in hepatocellular carcinoma [ 13 ], colorectal cancer [ 14 , 16 , 17 ], bladder cancer [ 15 ], gastric cancer [ 18 ], childhood ETV6/RUNX1-positive acute lymphoblastic leukemia [ 19 ], and papillary thyroid carcinoma [ 20 ], where METTL14 functions as a tumor suppressor [ 13 18 ], whereas levels of METTL14 expression are high in pancreatic cancer [ 21 , 22 ] and acute myeloid leukemia [ 23 ], where this protein functions as a tumor promoter. In breast cancer, contrasting findings have been reported from analyses of the expression and function of METTL14.…”
Section: Introductionmentioning
confidence: 99%